Padronização de ténica para recuperação de ovos de Toxocara canis em solo - Magoti, Luciana Puga (2008)
The purpose of this study was to standardize a flotation technique for the recovery of Toxocara canis eggs from soil, comparing different steps. The tests were done under standardized conditions on 1 g of previously sterilized soil samples contaminated experimentally with 200 eggs of T. canis. The following variables were evaluated in serial steps: sieving; type of wash; time of stirring; resuspention of sediment; solution flotation. Centrifuge-flotation in sodium nitrate (d= 1,20) was adopted as an initial technique, using Tween 80 (0.2%) and decinormal sodium hydroxide as solutions for washing the samples. Ten tests were made to compare the variables, using counting in triplicate. The sieving of the material reduced the recovery of eggs in a significant difference (p<0.001) and the number of eggs recovered were higher when the sediment was resuspended (p<0.05). After standardization, flotation solutions sodium chloride, zinc sulphate, sodium dichromate, magnesium sulphate, and sodium nitrate (d= 1,20) were compared. There was a significant difference between zinc sulphate and sodium chloride (p<0.05). In conclusion, the chance of recovering T. canis eggs from samples using flotation solutions can be increased by using resuspended sediment. On the other hand, the sieving procedure can drastically reduce the number of eggs.